Comparative Research on the Modernization of Chinese and Japanese National Traditional Sports from a Culturology Perspective. Issue 15 (2nd November 2018) - Lu, Li; Pan, Dong
Abstract: The modernization of Chinese and Japanese national traditional sports is here discussed using cultural comparative methods based on a dual construction theory of 'inner core–outer edge' according to the cultural classification principle. The paper concludes that, in the initial stage of the modernization of Chinese and Japanese traditional sports attributable to the eastward spread of Western culture through the cultural temporal and spatial space, cultural characteristics, nature, and internal adjustment mechanisms are major causes of the differences in the modernization process between Chinese and Japanese national traditional sports. Time lags existed in the modernization process in temporal, spatial, and subjectivity characteristics. This paper interprets the modernization process of Chinese traditional sports and explores useful implications for the transformation strategies and approaches to transformation.